Probing magnetic pulse welding of aluminium and steel sheets. (December 2021) - Shotri, Rishabh; Racineux, Guillaume; De, Amitava
Abstract: Magnetic pulse welding is used to join overlapped thin sheets of dissimilar materials in solid state, which is not easy by fusion welding due to severe thermomechanical distortion and the formation of brittle intermetallic compounds. An intense electromagnetic pulse is employed that causes an impact between the overlapped parts leading to plastic deformation and rapid coalescence along the interface thereby posing a challenge to monitor the evolution of joint. An effort combining experimental investigation and numerical process modelling is presented here for a quantitative understanding of magnetic pulse welding of thin AA5754 and DC04 steel sheets with a flat linear coil of Cu-OFHC alloy. The numerical model couples an electromagnetic and a dynamic mechanical analysis to compute the transient electromagnetic pressure and the progressive impact between the parts and the plastic deformation that the parts experience for a given coil and sheet geometry and materials. The computed results of the impact velocity of the flyer on the target, the top and bottom part in the overlapped assembly, and the flyer–target contact length are examined against the corresponding experimentally measured results for several process conditions. The computed results are further used to elucidate the progressive nature of the evolution of the joint. Overall, the computational model has served as an important tool to uncover the underlying phenomena and identify suitable range of process conditions to produce a defect-free weld in magnetic pulse welding of sheets. Highlights: Magnetic pulse welding between aluminium and steel thin sheets is investigated. A coupled transient electromagnetic and dynamic mechanical analysis is undertaken. Flyer impact velocity on target is measured by Photon Doppler Velocimetry (PDV). Evolution of elliptical ring-shaped welds for various process conditions is probed. Suitable ranges of flyer impact velocity and collision velocity are conjectured.